The modular design of trajectory compensation based on ATCF for precision motion control. (1st January 2020) - Wang, Ze; Hu, Chuxiong; Zhu, Yu; Zhang, Ming; Zhang, Chi
Highlights: Numerical calculation algorithm is used in the proposed algorithm to obtain accurate contouring error even in the extreme cases with high speed, large curvature and sharp corner. Based on the estimated contouring error, the Accurate Task Coordinate Frame is constructed, in which the contouring error and the related distance error can be decoupled and expressed easily. Through the gain adjustment for the above two errors, the optimal trajectory compensation is determined and fed back to the position loop to improve contouring performance. The effectiveness of the proposed ATCF method has been demonstrated by theoretical analysis and a series of experiments. Abstract: To achieve excellent contouring motion control without affecting the structure of original closed-loop controller, a modular design of trajectory compensation based on accurate task coordinate frame (ATCF) is proposed in this paper for precision multi-axis systems. Specifically, the contouring error point, i.e., the point located on the reference contour which is closest to the actual one, is obtained by the numerical computation method. Due to the accurate calculation through the above method, the calculated contouring error point can almost overlap with the actual one even under extreme contouring tasks with high speed, large curvature and sharp corner. Based on the estimated contouring error point, actual point and the desired point, ATCF is constructed. The coordinates of the desired point in ATCF represent the distance error and the contouring error, respectively. Through the trajectory compensators with reasonable gains adjustment, these two errors are fed back to the position loop of the system to modify the reference trajectory and to improve contouring control performance. Comparative experiments under various contouring control tasks are conducted to validate the practical effectiveness of the proposed ATCF scheme. The experimental results illustrate that the proposed scheme can achieve not only nearly perfect contouring error estimation but also obvious improvement of contouring accuracy compared with individual axial control and CCC.